2004
DOI: 10.2105/ajph.94.7.1218
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Incidence of HIV, Hepatitis B Virus, and Hepatitis C Virus Infections Among Males in Rhode Island Prisons

Abstract: High infection prevalence among inmates represents a significant community health issue. General disease prevention efforts must include prevention within correctional facilities. The high observed intraprison incidence of HBV underscores the need to vaccinate prison populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
193
3
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(218 citation statements)
references
References 33 publications
8
193
3
14
Order By: Relevance
“…The high prevalence of lifetime incarceration among STRIVE participants is not surprising given that previous studies have also shown higher rates of HCV and other blood-borne viruses among previously incarcerated individuals. [29][30][31] Finally, as shown in other research studies among IDUs, access to and utilization of health-care services are poor among this population. 32 It is important to note that a significant portion of this sample either did not have (31%) or were uncertain (12%) about their health-insurance coverage.…”
Section: Discussionsupporting
confidence: 52%
“…The high prevalence of lifetime incarceration among STRIVE participants is not surprising given that previous studies have also shown higher rates of HCV and other blood-borne viruses among previously incarcerated individuals. [29][30][31] Finally, as shown in other research studies among IDUs, access to and utilization of health-care services are poor among this population. 32 It is important to note that a significant portion of this sample either did not have (31%) or were uncertain (12%) about their health-insurance coverage.…”
Section: Discussionsupporting
confidence: 52%
“…While oversampling ICD9-coded records may also have inflated our results, applying the appropriate weighting to each subsample yielded a 26 % prevalence estimate which is remarkably consistent with previously reported rates in Rhode Island. 12,25,40 Only 42 % of patients had an available genotype. In the near term, this may impact costs but as more pangenotypic therapies become available in the next few years, genotype will become less of a cost driver.…”
Section: Discussionmentioning
confidence: 99%
“…14 Specific to the RIDOC population, studies have reported HCV prevalence rates from 23 to 27 %. 12,25,40,41 We conducted a cross-sectional survey of all incarcerations at RIDOC as of February 2014 and reviewed the electronic medical records (EMR) for data on screening uptake and clinical characteristics (see Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Se han observado altas prevalencias del virus de la hepatitis C en instituciones penitenciarias de Francia (4,9%), España (34,2% a 38,2%), Italia (38,2% a 90%), Australia (30,2% a 42%), Irlanda ((72%), Irán (45,4%), Ghana (18,7% a 19,2%), México (10%), Estados Unidos (13% a 23,1%) y Canadá (15,9% a 16,6%) (6,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). En América latina, los únicos datos publicados sobre la infección en reclusos provienen de Brasil, donde se han observado prevalencias de 4,8% a 41% (13,14,31).…”
unclassified